Coping Behavior of Correctional Inmates in a Correctional Institution - Muhammad Fikri Fauzi; DYP Sugiharto; Ali Formen (Study Program of Guidance and Counselling, Post Graduate Program, Universitas Negeri Semarang, 2024)
Correctional inmates have pressure in living their lives, so the behavior carried out by inmates in an effort to respond to this pressure is interesting. Adaptive coping behavior encourages the formation of one's positive attitude towards problems. This research attempted to obtain an overview of adaptive coping behavior in prisoners by employing a phenomenological qualitative design as the research approach applied through observation and semi-structured interviews with 7 respondents selected using purposive sampling. The result indicated, the respondents experienced problems such as lack of emotional control, disapproval of punishment, feeling guilty about family, lack of enthusiasm for life, feelings of resentment towards the company, feelings guilty about childhood and lack of ability to interact socially. The respondents exhibited coping behavior, such as accepting and surrendering (emotion-focused coping), planning a structured life (problem-focused coping), getting visits from family (social support), getting attention from their life partner (dyadic coping), performing reappraisal (positive reappraisal), having a strong character (character strength) and having the desire to memorize the Qur'an (religious coping). From these findings, it is known coping behavior affects an individual's personality. In this way, individuals will be able to adapt well to their environment. Exploring and applying coping behavior is highly recommended after this research.